UTILIZING FLIPPED LEARNING TO FACILITATE EFL STUDENTS' LISTENING COMPREHENSION: NON-FORMAL EDUCATION TEACHERS' PRACTICES AND CHALLENGES - Yuza, Silvina (2023)
Despite recognizing listening as an essential skill in language learning, research on effective teaching methods remains limited, particularly regarding the use of flipped learning as a notable learning model. This study aims to address this gap by investigating teachers' practices in facilitating students' listening comprehension under flipped learning model and the challenges they encounter when utilizing flipped learning. The study employed a qualitative case study involving two teachers and six EFL students enrolled in a non-formal education program in Jambi. Data collection methods included document analysis, observation, and multiple interviews. The findings reveal that flipped learning facilitates students' listening comprehension through both out-of-class and in-class activities. Out-of-class activities provide language input, repeated exposure and media support, and also accommodating self-paced learning. Consequently, it facilitates students in addressing their listening difficulties and preparing them better for in-class activities. In-class activities, particularly through reviewing activities to reinforce vocabulary and pronunciation concepts, greatly benefiting listening exercises. The study also identified four teacher strategies employed in this context namely gamified activities, group discussions, listening-speaking integrated activities, and answer sharing and presentations which promote learning quality improvement in listening class. However, various challenges were also identified, including those related to students, operational aspects, and teachers. To address these challenges effectively, the study recommends utilizing more well-designed out-of-class and in-class activities. This demands regular training for teachers in institutions that have adopted the flipped learning model to enhance their understanding of the utilization of flipped learning. Keywords: Flipped learning, flipped material, in-class activities, listening comprehension, non-formal education, out-of-class activities.